2005
DOI: 10.1177/1523422305279681
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Protégé Race, Gender, and Proactive Socialization Attempts on Peer Mentoring

Abstract: The problem and the solution. A within-subjects design was used to examine the roles of newcomer race, gender, and proactive socialization attempts on potential mentors' willingness to engage in peer mentoring. In this laboratory study, 110 White college students participated. Participants were encouraged to participate as mentors in a new peer mentoring program and were provided with the profiles of 12 potential protégés and asked to evaluate each. Results of repeated-measure ANOVA suggested that female parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A broader range of structural characteristics have been investigated within the social capital literature, which is not surprising given the definitional constraints of the social ties within the mentoring literature. Studies of peer mentoring (Ensher, Thomas, & Murphy, 2001;Kram & Isabella, 1985;Thomas, Hu, Gewin, Bingham, & Yanchus, 2005) and comparisons of supervisory versus nonsupervisory mentoring (Payne & Huffman, 2005;Scandura & Williams, 2004) are examples of how structural characteristics have been explored in the mentoring literature. Further insights into mentoring may be gained by incorporating additional structural concepts into future research, such as the concept of network diversity included in Higgins and Kram's (2001) typology of developmental networks.…”
Section: Discussionmentioning
confidence: 99%
“…A broader range of structural characteristics have been investigated within the social capital literature, which is not surprising given the definitional constraints of the social ties within the mentoring literature. Studies of peer mentoring (Ensher, Thomas, & Murphy, 2001;Kram & Isabella, 1985;Thomas, Hu, Gewin, Bingham, & Yanchus, 2005) and comparisons of supervisory versus nonsupervisory mentoring (Payne & Huffman, 2005;Scandura & Williams, 2004) are examples of how structural characteristics have been explored in the mentoring literature. Further insights into mentoring may be gained by incorporating additional structural concepts into future research, such as the concept of network diversity included in Higgins and Kram's (2001) typology of developmental networks.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three articles address the individual and contextual factors of protégé gender and race, virtual mentoring, and the ethics of mentoring that affect the field of HRD broadly in terms of application. Thomas, Hu, Gewin, Bingham, and Yanchus (2005) help close the gap in the research on access to mentoring through examining the roles of protégé race and gender in mentors' willingness to serve as a peer mentor. Bierema and Hill (2005) and McDonald and Hite (2005) provide much-needed insight into the contextual issues associated with virtual mentoring and ethics, which are important to our understanding of mentoring practices in HRD.…”
Section: Training and Developmentmentioning
confidence: 99%
“…One could accept the predominance of ethnic and sexual orientation matching and conclude that students are choosing programs with faculty similar to themselves. Although ethnic and sexual orientation matching could be seen as providing mentees with understanding and support, it may also serve to promote complacency if it means that faculty are preferring mentees because they remind them of themselves (Thomas, Hu, Gewin, Bingham, & Yanchus, 2005). Since prior researchers have found that graduate students felt that the quality of the mentorship provided from people similar to themselves was better, perhaps a both-and track is best.…”
Section: Participants' Description Of Their Mentorsmentioning
confidence: 98%